2021
DOI: 10.1137/20m1367660
|View full text |Cite
|
Sign up to set email alerts
|

Finding Large $H$-Colorable Subgraphs in Hereditary Graph Classes

Abstract: We study the Max Partial H-Coloring problem: given a graph G, find the largest induced subgraph of G that admits a homomorphism into H, where H is a fixed pattern graph without loops. Note that when H is a complete graph on k vertices, the problem reduces to finding the largest induced k-colorable subgraph, which for k = 2 is equivalent (by complementation) to Odd Cycle Transversal.We prove that for every fixed pattern graph H without loops, Max Partial H-Coloring can be solved: in {P5, F }-free graphs in poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Let us point out that all mentioned hardness proofs rule out the existence of subexponential-time algorithms, unless the ETH fails. Furthermore, all algorithmic results hold even for L k C , except for the case (k, t) = (4,6), which is NP-complete in the list setting [20].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Let us point out that all mentioned hardness proofs rule out the existence of subexponential-time algorithms, unless the ETH fails. Furthermore, all algorithmic results hold even for L k C , except for the case (k, t) = (4,6), which is NP-complete in the list setting [20].…”
Section: Introductionmentioning
confidence: 92%
“…First, Chudnovsky et al [3] showed that for k ∈ {5, 7, 9}∪ [10; ∞), the LH (C k ) problem can be solved in polynomial time for P 9 -free graphs. Very recently, Chudnovsky et al [4] studied some further generalization of the homomomorphism problem in subclasses of P 6 -free graphs. Furthermore, the already mentioned 2 O( √ n log n) -time algorithm by Groenland et al [21] actually works for LH (H) for a large family of graphs H: the requirement is that H does not contain two vertices with two common neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 6 has other applications as well. For a graph G, let ω(G) denote the size of a maximum clique in G. Chudnovsky et al [9] gave for the class of (K 1 1,3 , P 6 )-free graphs, an n O(ω(G) 3 ) -time algorithm for Max Partial H-Colouring, a problem equivalent to Independent Set if H = P 1 and to Odd Cycle Transversal if H = P 2 . In other words, Max Partial H-Colouring is polynomial-time solvable for (K 1 1,3 , P 6 )-free graphs with bounded clique number.…”
Section: Corollarymentioning
confidence: 99%
“…In other words, Max Partial H-Colouring is polynomial-time solvable for (K 1 1,3 , P 6 )-free graphs with bounded clique number. Chudnovsky et al [9] noted that Max Partial H-Colouring is polynomial-time solvable for graph classes whose mim-width is bounded and quickly computable. Hence, Theorem 6 generalizes their result for Max Partial H-Colouring to (K 1 1,s , P t )-free graphs with bounded clique number, for any s ≥ 1 and t ≥ 1.…”
Section: Corollarymentioning
confidence: 99%
See 1 more Smart Citation